ANALISIS KOMPARASI KINERJA REKSADANA PENDAPATAN TETAP BAGI HASIL (SYARIAH) DENGAN INDEKS LQ45 MENGGUNAKAN METODE SHARPE, JENSEN DAN TREYNOR - Ayu Rahmawati; Wida Purwidianti (Media Ekonomi, 2015)
This research was aimed at knowing the mutual fund’ performance of fixed-incom profit sharing (syariah) and comparing it to LQ45 indeks through sharpe, Jensen and Tteynor method in 2012. The proposed hypothesis was that there was a significant defference between the mutual funds’ performance of fixed-incom profit sharing (syariah) and comparing it to LQ45 indeks through sharpe, Jensen and Treynor method. The method of this reaserch was descriptive qualitative even though the data obtained was quantitatuf data. The population of this research was the fixed-income mutual funds which actively operated in Indonesia reffering to BAPEPAM during 2012. Thesample was taken through purposive sampling. There were 7 mutual funds which were analyzed. The data which were used in this research was the data of monthly NAB. Therefore the data wara totally 84 items. The data analysis was through paired sample-test. The result of this research was that the mutual funds’ performance of fixed-income profit sharing (syariah) with the method of sharpe was better than the performance of LQ45 with the average score 1224.83 while the LQ45 index score was -0.003608758. however, the statistical test did not show thesignificant difference. By using treynor method, both the mutual funds’ performance of fixed-income profit sharing (syariah) and LQ45 index were similarly positive, but the t-test computation did not show the significant difference. In addition, by using Jensen method, there was no significant difference between the mutual funds’ performance of fixed-income profit sharing (syariah) and LQ45 index after the t-test computation. Keywords: the mutual funds’ performance of fixed-income profit sharing (syariah), sharpe, Jensen and treynor method.